Metafora konseptual sebagai kritik sosial berbentuk tagar politik - Alfiani, Ranti; Ajie, Muhammad Arie Andhiko (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Political contestation often produces linguistic phenomena that are interesting to study, such as the presence of metaphorical hashtags. This study examines conceptual metaphors in viral political hashtags during the 2024 General Election on social media, specifically #AnakHaramKonstitusi, #TolakPolitikDinasti, and #BauKetekOligarki. The objective of this research is to contribute to the understanding of conceptual metaphors in social media, particularly their function as a form of social critique on political issues. These three hashtags are the main data to be studied. Conceptual metaphors provide a way to understand abstract concepts through concrete experiences and create connections between the source and target domains. This research uses a descriptive qualitative method with cross-domain theory-based analysis to map the metaphorical relationships in these hashtags. The results show that these political hashtags reflect public thoughts and emotions towards political dynamics, such as injustice, nepotism, and oligarchic domination. The image scheme underlying these hashtags is identity matching, which creates a meaning match between linguistic symbols and socio-political reality. Through metaphorical language, these hashtags become an effective tool in voicing social criticism and building public awareness about complex political issues.